2018
DOI: 10.1007/s11356-018-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on phthalate exposure and human health: a special focus on liver toxicity and stem cell regeneration

Abstract: Phthalates have been blended in various compositions as plasticizers worldwide for a variety of purposes. Consequently, humans are exposed to a wide spectrum of phthalates that needs to be researched and understood correctly. The goal of this review is to focus on phthalate's internal exposure pathways and possible role of human digestion on liver toxicity. In addition, special focus was made on stem cell therapy in reverting liver toxicity. The known entry of higher molecular weight phthalates is through inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 68 publications
1
42
0
1
Order By: Relevance
“…Human phthalate exposures were associated with the increased risks of metabolic disorders, including obesity, diabetes, insulin resistance, and deteriorated liver function [ 53 , 54 , 55 ]. Chronic exposures can lead to the continuous accumulation and intensive detoxification of phthalates in the liver [ 56 ]. Thus, liver cells are likely to be exposed to the highest concentration of phthalates in the body [ 57 ], and it is crucial to understand the liver toxicity of phthalates.…”
Section: Discussionmentioning
confidence: 99%
“…Human phthalate exposures were associated with the increased risks of metabolic disorders, including obesity, diabetes, insulin resistance, and deteriorated liver function [ 53 , 54 , 55 ]. Chronic exposures can lead to the continuous accumulation and intensive detoxification of phthalates in the liver [ 56 ]. Thus, liver cells are likely to be exposed to the highest concentration of phthalates in the body [ 57 ], and it is crucial to understand the liver toxicity of phthalates.…”
Section: Discussionmentioning
confidence: 99%
“…5 Epidemiological data suggest that DBP is responsible for adverse hepatic effects. 6,7 Animal studies have also shown that DBP is a reproductive and developmental toxin. 8 Although DBP does not accumulate in any organ shortly after administration, over the long term, it will be found primarily in the liver and kidney.…”
Section: Introductionmentioning
confidence: 99%
“…17, No. 4 (December 2018) Trasande et al, 2013;Kay et al, 2014;Choi et al, 2017;Praveena et al, 2018). 따라서 본 연구에서는 생체시료 중 농도를 이용하여 프탈레이트 노출에 대한 주요 영향요인을 분석하고, 인 체 노출 시나리오를 정립하여 일일섭취노출량 및 위해 수준을 평가하고자 하였다.…”
Section: 서 론unclassified